2007
DOI: 10.1002/marc.200600635
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and Doping of Polyaniline Emeraldine Base in Imidazolium Ionic Liquids Investigated by Spectroscopic Techniques

Abstract: Polyaniline is a model molecular system in the study of conductive polymers. Ionic liquids, on the other hand, are becoming more and more a very convenient alternative for conventional organic solvents. The dissolution of polyaniline‐emeraldine base (PANI‐EB) in imidazolium ILs leads to its doping, as indicated by optical and resonance Raman spectroscopies. In this study, it is proposed that the interaction of PANI‐EB and imidazolium ILs involves the specific interaction of the quinoid moiety of the former wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Ionic liquids, organic salts that are liquid at low temperature, have also been used as synthetic media for the preparation of nanostructured conducting polymers [21,22]. Uniform nanofibers have also been prepared by polymerization at an aqueous-organic interface [14,15].…”
Section: -D Zeolitesmentioning
confidence: 99%
“…Ionic liquids, organic salts that are liquid at low temperature, have also been used as synthetic media for the preparation of nanostructured conducting polymers [21,22]. Uniform nanofibers have also been prepared by polymerization at an aqueous-organic interface [14,15].…”
Section: -D Zeolitesmentioning
confidence: 99%
“…Different authors have reported the doping process of polyaniline base by imidazoliumbased ionic liquid [45][46]. In the present work, the improvement of the conductivity by using the phosphonium -based IL may be attributed to the interactions between the IL and the polyaniline chains contributing for an additional doping level.…”
Section: And Ac Electrical Conductivitymentioning
confidence: 75%
“…This sample also presents smaller surface area. In this case, the ILmimC 10 COOH.Br being more hydrophobic, are not located inside the water droplets, contributing for the formation of PAni.DBSA with larger particle size, probably due to the p-p or cation-p interactions between the imidazolium ring and the benzenoid/ quinoid rings of PAni, as also discussed in the literature [38,39]. Such interactions and the strong tendency of imidazolium-based ILs towards self assembly contribute for the increase in particle size and also for a more compact morphology, as indicated by SEM analysis.…”
Section: Morphological Characteristicsmentioning
confidence: 88%